2021
DOI: 10.1182/blood-2021-151566
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Temporal Changes in Anticoagulation Treatment Patterns in Patients Diagnosed with Cancer-Associated Thrombosis: An Oscar-US Analysis

Abstract: Background: Although guidelines include direct-acting oral anticoagulants (DOACs) as an alternative to low molecular weight heparins (LMWHs) for treatment of cancer associated venous thrombosis (CAT), specific recommendations for selection of patients for DOAC treatment vary. Recommendations for use of DOACs are driven predominantly by perceptions of risk: benefit ratio (often associated with different cancer subtypes). We sought to assess patient characteristics and temporal changes in DOAC (vs. LMWH) utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Based on previous analyses of this Optum EHR dataset, we anticipated approximately 6,000 patients experiencing Ca-VTE, of which, >1,000 patients would have received rivaroxaban and >1,000 would have received apixaban. 16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous analyses of this Optum EHR dataset, we anticipated approximately 6,000 patients experiencing Ca-VTE, of which, >1,000 patients would have received rivaroxaban and >1,000 would have received apixaban. 16 …”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that rivaroxaban would have similar effectiveness and safety to apixaban with respect to the risk of recurrent VTE or any bleed resulting in hospitalization, defined as an upper limit of the 95% confidence interval (CI) for the hazard ratio (HR) of <1.50 15 and a one-sided alpha level of 0.025. 15 Assuming a 3-month risk of the primary outcome of 7% 15,16 and no difference between rivaroxaban and apixaban (i.e., HR: 1.0), we estimated a sample of approximately 1,900 patients would be required to observe an expected total of 100 primary outcome events and would give our study 80% power. Based on previous analyses of this Optum EHR dataset, we anticipated approximately 6,000 patients experiencing Ca-VTE, of which, >1,000 patients would have received rivaroxaban and >1,000 would have received apixaban.…”
Section: Sample Sizementioning
confidence: 99%
“…This study is part of the OSCAR program with independent studies in the United States, 10,20 United Kingdom, 13 and Sweden 24 that use consistent definitions of design, exposures of interest, covariates, and data analyses. While the study in Sweden is being reported, the comparison of the UK and U.S. 20 cohorts of the OSCAR program indicates that the study findings are generalizable to patients with active cancer not including non-brain central nervous system, unresected colorectal/lower gastrointestinal tract, hematologic (except lymphoma and myeloma), esophagus, stomach, and bladder cancer and patients with conditions such as thrombocytopenia, end-stage kidney disease, and current pregnancy.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…The recognition of patients with CT at high risk of bleeding was guided by expert interpretation of the International Society on Thrombosis and Haemostasis (ISTH) guidance. 6 The Observational Studies in Cancer Associated Thrombosis for Rivaroxaban in the United Kingdom Cohort (OSCAR-UK) is part of the OSCAR program with independent studies in the United States, 10 United Kingdom, 11 and Sweden. 12…”
Section: Introductionmentioning
confidence: 99%